Studies on Some Biologically Important Ternary Complexes of Nickel(II) with 2-(2´ -Hydroxyphenyl) Benzimidazole and Acids - SETH, GITA; GARG, YAJULA; K. MOURAYA, NARENDRA (Asian Journal of Chemistry, 2010)
Some new antifungal nickel(II) complexes of 2-(2'-hydroxyphenyl) benzimidazole (HPBI) and amino acid, carboxylic acid and phenol have been synthesizd and characterized on the basis of their elemental analysis. conductance measurement, IR and NMR studies. These complexes were screened for their antifungal activities against Alternaria alternata and Aspergillus niger and compared with Dithane M-45, a commercial fungicide.